Fluid-Solid conjugate heat transfer modelling using weakly compressible smoothed particle hydrodynamics - Ng K.C.; Ng Y.L.; Sheu T.W.H.; Mukhtar A. (Elsevier Ltd, 2023)
Heat conduction; Heat exchangers; Heat flux; Parallel flow; Problem solving; Reynolds number; Rhenium compounds; Thermal conductivity; Conjugate heat transfer; Shifting; Smoothed particle hydrodynamics; Tensile instabilities; Weakly-compressible; Hydrodynamics